IDENTIFIKASI MISKONSEPSI SISTEM SARAF PADA BUKU TEKS BIOLOGI KELAS XI - Irma Hidayati; Abdullah; Mustafa Sabri (Universitas Islam Negeri Ar-Raniry, 2015)
This study entitled â€œIdentifying the misconceptions in nervous system in12th Grade of biology textbookâ€ aims to identify misconception on biology textbooksâ€™ about nervous system. The method of the research was descriptive. The objects of the research were 7 of biology textbooks for grade xi published within the last 5 years. The national education regulation no. 1 year 2011, 4 january 2011 states that the textbook used at school should be at least in the last 5 years. The instrument used were observation sheet to compare the concept of the investigated book to the foreign source textbook as guidance. The results showed that there were misconceptions in the material of nerve system contained in 7 textbooks investigated, they were in the concept of structure and function of nervous, impuls, central nervous system and peripheral nervous system.